Entry in German pharmacy market - Oliver Arentz; Clemens Recker; Van Anh Vuong; Achim Wambach (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2016)
[Introduction] Over the last few years there has been an increasing debate on supply security in the German healthcare system. In particular, concerns have been raised with respect to the shortage of pharmacies in rural regions. While the low level of demand for pharmaceutical services and products in these in these areas dampens the profitability of pharmacies, regulations imposed on pharmacies with substantial implications for their cost structures affect the entry and exit decisions of pharmacies in rural district, and hence directly affecting the supply gap. In this article we estimate a model of entry for pharmacies in Germany and identify the economic forces determining market entry. Our empirical model captures important features of the pharmacy market. First, the toughness of short-run competition reflect the idea that an increase in the number of pharmacies in a given market lowers the profits that can be earned by all participants. Second, potential entrants face an amount of fixed entry cost lowering the net profit level and affect firm's entry decision. Furthermore, we allow the magnitude of the fixed cost to differ across firms and allowing different firms to earn different levels of profit in a given market and therefore allow for markets with similar characteristics to support different numbers of pharmacies. This feature allows markets with similar structures to have different numbers of pharmacies. We estimate the model using a constructed dataset on the number of pharmacy stores operating in 4115 geographic markets in Germany. In addition to in-formation on market characteristics such as population number and demographic structure, we also measure the number of branches a pharmacist operates. The number of branches captures information on possible scale effect affecting the level of firm's fixed cost. The model estimates describe the pharmacies' profitability and the longrun market structure. Furthermore, using the estimates we can also assess the effect different policy measure on market structure, for instance the effect of entry subsidy, the relaxation of operation requirements that have cost impacts, or indirect subsidy through altering market characteristics. The next section provides information on the regulation of pharmacies in Germany and Europe and summarizes the observed market structure in the data. The third section describes the empirical model used for the analysis and outlines our estimation procedure. At this stage the model estimates on the competition effect and importance of firm heterogeneity and the entry fixed cost are still work in progress. The fourth section provides outlook on possible counterfactual exercises and conclude.
Keywords: 330; Markteintritt; Pharmahandel; Marktstruktur; Deutschland